MODERN APPROACHES TO PUBLIC PROTECTION AGAINST INDOOR RADON. INTERNATIONAL REGULATORY EXPERIENCE - S. M. Kiselev; M. V. Zhukovsky (Радиационная гигиена)
Intensive worldwide researches of the public exposure to radon are carried out for over 30 years. According to numerous studies being performed in many countries, radon and its progenies contribute significantly in total dose to the public. At that, dose due to inhalation of radon and its progenies is higher than that induced by other radiation sources, including sources used in medicine and those occurring in the environment due to the nuclear fuel cycle activities. Prolonged internal exposure to the human‘s body induced by the radon decay products is one of the key factors in the development of the lung cancer pathology. The recent results of global epidemiological studies, aimed at the risk assessment of indoor radon-induced lung cancer, have initiated the need to improve approaches to the regulation of this problem. International organizations (such as WHO, IAEA, ICRP) proposed a strategy of the public radiation protection against radon exposure and adapted this strategy to the up-to-date realities. The recent recommendations not only correct the radon activity concentration being limited in dwellings, but also change its status through converting the action level to the reference one. The strategies for limitation of the public exposure due to this component of natural radiation should be revised at the national level and an action plan for their implementation in the long term perspective should be developed. This paper deals with the key provisions of the recent international recommendations including approaches to regulate the public protection against radon exposure.